Successful invasion: camera trap distance sampling reveals higher density for invasive raccoon dog compared to native mesopredators - Selonen, Vesa (Springer Nature, 2025)
Monitoring population parameters of invasive species gains importance as these species continue to expand all over the world. Monitoring of invasive mammalian mesopredators is, however, complicated due to their nocturnal and secretive behaviour. In the European Union, the most common invasive mesopredator is the raccoon dog (Nyctereutes procyonoides), which causes concerns for native species, such as endangered waterfowl that may be subject to nest predation. We studied the density of mesopredators in southern Finland with wildlife cameras, using methodology of distance sampling. We deployed in total of 175 camera traps around 11 (spring 2020) and 16 (spring 2021) lakes or wetlands. We inferred densities for raccoon dogs, and for native mesopredators the red fox (Vulpes vulpes) and the European badger (Meles meles) for comparison. Raccoon dogs were found to have higher overall as well as site-specific densities (about 3.7 ind./km2) than badgers (1.2 ind./km2) and red foxes (0.6 ind./km2). The raccoon dogs also were present at every study wetland, while badgers were not found at all sites. The red fox showed more diurnal activity compared to raccoon dogs and badgers. Camera trap distance sampling enabled us to provide a density estimates on a rather small spatial and temporal scale for species of similar size and movement speed. It could therefore prove valuable as a long-term monitoring option, as climate trends are likely to further enable raccoon dog expansion. Currently this invasive species appears to be the most common mesopredator around wetlands in the southern boreal zone of southern Finland.